Preparation method and application of niobium boride-niobium oxide complex phase three-dimensional material
By using niobium boride-niobium oxide complex phase three-dimensional materials in lithium sulfur batteries and lithium ion batteries, the performance and safety problems of the battery under low temperature and fast charging conditions are solved, and the cycling stability and rate performance are achieved, and high discharge capacity and fast charging characteristics are provided.
Patent Information
- Application Number
- CN202510078241.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Lithium-ion batteries and lithium-sulfur batteries have battery performance and safety problems under low temperature and fast charging conditions, especially the growth of lithium dendrites and the electrical insulation of polysulfides lead to a decrease in the electrochemical reaction rate and poor circulation and rate performance.
The three-dimensional niobium boronide-niobium oxide complex phase is used as the host material of lithium sulfur batteries and the negative electrode material of lithium ion batteries. Through its unique heterogeneous interface and built-in electric field effect, the "shuttle effect" of polysulfide is suppressed, the charge-to-movement mechanics are improved, and the transformation of elemental sulfur to polysulfide is promoted.
It significantly improves the cycle stability and rate performance of lithium-sulfur batteries at low temperatures, and provides high discharge capacity and fast charging characteristics for lithium-ion batteries, with good application prospects.
Smart Images

Figure CN119852412A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a preparation method and application of a niobium boride-niobium oxide composite three-dimensional material. Background Art
[0002] With the rapid development of high-energy-consuming electronic devices, new energy vehicles and drone industries, people have paid attention to high-power density secondary batteries, thus achieving new breakthroughs in fast charging technology. Lithium-ion batteries have become the most advanced electrochemical energy storage systems in portable electronic devices, energy storage stations and electric vehicles due to their advantages such as high energy density and long cycle stability, and have attracted widespread attention from countries around the world. It is well known that negative electrode materials are the bottleneck in the development of high-power lithium-ion batteries. Graphite has a high theoretical capacity (372mAh g -1 ) is widely used as a commercial negative electrode material for lithium-ion batteries. However, its lithium insertion potential is low (0.1V vs.Li + / Li), which easily promotes the growth of lithium dendrites under low temperature and fast charging conditions, seriously affecting battery performance and safety. Therefore, there is an urgent need to find a high-power, high-specific-energy lithium-ion battery negative electrode material.
[0003] As a new energy storage system that surpasses lithium-ion batteries, lithium-sulfur batteries are based on conversion-type positive electrodes, in which active sulfur (S8) and lithium sulfide Electrochemical redox reaction occurs between the two, showing an extremely high theoretical energy capacity (1675 mAh g -1 ), which is about ten times the theoretical energy density of common mainstream lithium-ion batteries. In addition, the theoretical energy density of lithium-sulfur batteries (2600Wh Kg -1 ) is high and the natural reserves of elemental sulfur are abundant, the cost is lower, and it is environmentally friendly, making it the next generation of secondary batteries with the greatest application potential. However, the practical application of lithium-sulfur batteries still faces the following key challenges: the electrical insulation of soluble intermediate polysulfides (Li2S8, Li2S6 and Li2S4) and solid sulfur species (S8, Li2S2 and Li2S) leads to a decrease in the electrochemical reaction rate, thereby reducing the utilization rate of active materials, especially under low temperature conditions; the tricky "shuttle effect" caused by the slow redox reaction kinetics of polysulfides will cause a large amount of active materials to be lost, ultimately leading to a decrease in the reversible capacity of the battery; the large volume change of the S positive electrode during the cycle will cause the electrode active material to fall off; the violent reaction of lithium polysulfides on the surface of the lithium negative electrode and repeated uneven deposition will cause corrosion and pulverization of metallic lithium, destroying the structure of the lithium anode, especially under high sulfur loading and poor electrolyte conditions. Summary of the invention
[0004] Based on the above technical background, the present invention provides a niobium boride-niobium oxide composite three-dimensional material. The three-dimensional nanoscale material can be used as a host material for the sulfur positive electrode of a lithium-sulfur battery to alleviate the "shuttle effect" of polysulfides and improve the cycle performance and rate performance of lithium-sulfur batteries at low temperatures; it can also be used as a negative electrode material for lithium-ion batteries, exhibiting high discharge capacity and fast charging characteristics.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a niobium boride-niobium oxide composite three-dimensional material, comprising the following steps:
[0007] The niobium source and the boron source are dissolved in a solvent containing an alkaline solution in a molar ratio of 1:1.2-2.3, a surfactant is added, and the reaction is stirred at 0-120°C for 3-24 hours under a protective atmosphere. After the reaction, the products are centrifuged and collected with distilled water and anhydrous ethanol respectively, and then dried to obtain a niobium boride-niobium oxide composite three-dimensional material.
[0008] The stirring method is magnetic stirring or mechanical stirring, and the mixing time is 2-8 hours. The centrifugal speed is 5000-9000r / min, and the centrifugal time is 3-6 minutes each time.
[0009] Furthermore, the niobium source includes one of niobium pentachloride, niobium ethanol, niobium oxalate, ammonium niobate oxalate and niobium pentoxide; the boron source includes one of boron dioxide, sodium borohydride and boron powder; the alkaline solution includes one or more combinations of sodium hydroxide, potassium hydroxide and ammonia water; the solvent includes one or more combinations of ultrapure water, oleylamine, ethanol, cyclohexane, isopropanol, glycerol, tetrahydrofuran, N-methylpyrrolidone and ethylene glycol; the surfactant includes one or more combinations of cetyltrimethylammonium bromide (CTAB), ethanolamine and polyvinylpyrrolidone (PVP).
[0010] Furthermore, the amount of alkaline substance in the alkaline solution is 0.5-2 times the molar ratio of the niobium source, and the amount of surfactant is 0.4-3 times the molar ratio of the niobium source.
[0011] An application of a niobium boride-niobium oxide composite three-dimensional material prepared by the method, wherein the niobium boride-niobium oxide composite three-dimensional material is used as a host material of sulfur in a lithium-sulfur battery or as a catalyst alone for adsorbing polysulfides.
[0012] Furthermore, when applied to lithium-sulfur batteries, the niobium boride-niobium oxide composite three-dimensional material is evenly mixed with graphyne to form a composite material, the composite material and the active material sublimated sulfur are ground and mixed into a uniform powder, which is transferred into a polytetrafluoroethylene reactor or a magnetic boat, and the container is placed in a blast drying oven or a tubular furnace and heated to 140-170°C for constant temperature reaction for 4-20 hours, and then naturally cooled to room temperature and taken out to obtain a mixture of sulfur, niobium boride-niobium oxide and graphyne, which is used as the positive electrode material of the lithium-sulfur battery.
[0013] Preferably, the heating temperature is 155° C. and the constant temperature reaction time is 15 h.
[0014] Furthermore, the mass ratio of the niobium boride-niobium oxide composite three-dimensional material to graphyne is 1:2-5, preferably, the mass ratio of the niobium boride-niobium oxide composite three-dimensional material to graphyne is 1:4; the mass ratio of the composite material to the active material sublimated sulfur is 2-4.5:6.5-8.5, preferably 3:7, 1:3, 2:8;
[0015] An application of the niobium boride-niobium oxide composite three-dimensional material prepared by the preparation method, wherein the niobium boride-niobium oxide composite three-dimensional material is used as a negative electrode active material in a lithium ion battery.
[0016] Furthermore, niobium boride-niobium oxide composite three-dimensional material is dispersed in a solvent as a negative electrode active material together with a conductive agent and a binder to obtain a negative electrode slurry, and the negative electrode slurry is coated on a current collector, heated and dried, rolled and punched to obtain a negative electrode sheet.
[0017] The binder is polyvinylidene fluoride (PVDF) or an aqueous dispersion of acrylonitrile multi-polymer (LA133), the conductive agent is acetylene black, and the solvent is N-methylpyrrolidone (NMP) or ultrapure water.
[0018] The negative electrode active material accounts for 70-95% of the total mass of the negative electrode material (negative electrode active material, conductive agent and binder), the conductive agent accounts for 2.5-20% of the total mass of the negative electrode material, and the binder accounts for 2.5-10% of the total mass of the negative electrode material. Preferably, the mass ratio of active material: conductive agent: binder is 90%:5%:5%.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) The niobium boride-niobium oxide composite three-dimensional material prepared by the present invention is in the shape of a three-dimensional hollow sphere with a diameter of about 300nm. The present invention applies niobium boride-niobium oxide (NbB-NbO2) to lithium-sulfur batteries for the first time, which can not only physically confine polysulfides and inhibit the diffusion of polysulfides, but also the built-in electric field formed at the heterogeneous interface can improve the charge transfer kinetics, promote the transformation of elemental sulfur to polysulfides, prevent catalyst passivation, and improve the cycle and rate performance of lithium-sulfur batteries at low temperatures; in addition, niobium boride-niobium oxide (NbB-NbO2) can be used as a negative electrode material for lithium-ion batteries, showing a high discharge specific capacity and fast charging performance, and has good application prospects.
[0021] 2) The preparation method of the present invention is simple, low-cost, has low requirements on equipment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the XRD pattern of the niobium boride-niobium oxide composite three-dimensional material synthesized in Example 1;
[0023] Figure 2 This is a SEM image of the niobium boride-niobium oxide composite three-dimensional material synthesized in Example 1;
[0024] Figure 3 The charge and discharge curve of the lithium-sulfur battery of Example 1 at 0.2C;
[0025] Figure 4 The charge and discharge curve of the lithium-sulfur battery in Example 1 at 0°C and 0.5C;
[0026] Figure 5 This is the SEM image of the niobium boride-niobium oxide composite three-dimensional material synthesized in Example 2. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] A synthesis of a niobium boride-niobium oxide composite three-dimensional material, comprising the following steps:
[0030] 0.811g of niobium pentachloride and 0.189g of sodium borohydride were added to a three-necked flask filled with argon gas and containing 70mL of ultrapure water, followed by 0.08g of sodium hydroxide, followed by mechanical stirring for 2h, and then 0.5g of CTAB was added, followed by mechanical stirring at 0℃ for 6h to make the above solutions evenly mixed, and then the above solutions were centrifuged with distilled water and anhydrous ethanol for three times at a speed of 7000 rpm, each time for 5 minutes, and the black product was collected and dried in a vacuum drying oven to obtain a niobium boride-niobium oxide composite three-dimensional material. The XRD spectrum is shown as follows: Figure 1 As shown, the positions of all diffraction peaks in the figure are consistent with the standard cards of NbO2 (JCPDS card no.43-2043) and NbB (JCPDS card no.32-0709). Figure 2 The SEM image of the prepared niobium boride-niobium oxide composite three-dimensional material is shown in Figure 1. As can be seen from the figure, the morphology of the niobium boride-niobium oxide composite three-dimensional material is hollow nanospheres with a diameter of about 300 nm.
[0031] The niobium boride-niobium oxide composite three-dimensional material obtained in this embodiment can be used alone as a catalyst for adsorbing polysulfides, and can also be used as a host material for lithium-sulfur batteries to inhibit the "shuttle effect" of polysulfides and improve the cycle stability and rate performance of lithium-sulfur batteries at low temperatures.
[0032] When applied to lithium-sulfur batteries, the prepared niobium boride-niobium oxide composite three-dimensional material is compounded with graphyne in a mass ratio of 1:4 to obtain a composite material, and the composite material is then evenly mixed with sublimated sulfur in a mass ratio of 1:3. Add it to an agate mortar and grind it for thirty minutes to finally fully mix it into a powder with uniform color. Pour the mixture on weighing paper and transfer it to a weighing bottle. Put the weighing bottle into the lining of a polytetrafluoroethylene reactor, heat it in a blast drying oven, and keep it at a constant temperature of 150°C for 15 hours. After the reaction is completed, wait for the reactor to cool to room temperature and take it out to obtain a mixture of sulfur, niobium boride-niobium oxide and graphyne.
[0033] A mixture of sulfur, niobium boride-niobium oxide and graphyne is used as the positive electrode material of the lithium-sulfur battery, metallic lithium is used as the negative electrode, and the amount of commercial ether electrolyte is 10uLmg -1 , assemble lithium-sulfur batteries and test electrochemical performance. The charge and discharge curves at 0.2C are as follows Figure 3 As shown, the discharge capacity of the first cycle is 1359.3 mAh g -1 , the charging capacity is 1300.5mAh g -1 , the coulombic efficiency is 95.67%. The cycle test was carried out at 0℃, and the charge and discharge curves are as follows Figure 4 As shown. The first cycle discharge capacity at 0.2C is 1051.9 mAh g -1, the charging capacity is 1035.1mAh g -1 ; The first cycle discharge capacity at 0.5C is 935.0mAh g -1 , the charging capacity is 928.1mAh g -1 Even at the 50th cycle, the discharge capacity is 690.5 mAh g -1 , charge capacity 690.0mAh g -1 , indicating that the assembled lithium-sulfur battery has good cycle stability.
[0034] Example 2
[0035] The difference between this embodiment and embodiment 1 is that 50 mL of distilled water solvent is replaced with 50 mL of isopropanol, and ethanolamine is added instead of CTAB, and the reaction conditions are changed to 6 hours at 25°C. The other parameters are the same as those in embodiment 1. The final niobium boride-niobium oxide is also a three-dimensional material. SEM images are shown in Figure 5 As shown, the three-dimensional hierarchical spherical material has a sphere diameter of about 300 nm.
[0036] The niobium boride-niobium oxide composite three-dimensional material obtained in this embodiment is used as a negative electrode active material in a button-type lithium ion battery. The three-dimensional hierarchical material can shorten the lithium ion diffusion distance, increase the effective contact area between the electrolyte and the interface, improve the charge transfer kinetics, and significantly improve the electrochemical performance of the lithium ion battery. The binder used is polyvinylidene fluoride (PVDF), the conductive agent is acetylene black, the solvent is N-methylpyrrolidone (NMP), and the negative electrode slurry is composed of 80% of the niobium boride-niobium oxide composite three-dimensional material, 10% of the conductive agent and 10% of the binder by mass percentage. The counter electrode of the assembled button battery is metallic lithium, and the electrolyte is LiPF6 / EC / DMC (1 mol / L).
[0037] Example 3
[0038] The difference between the preparation of niobium boride-niobium oxide composite three-dimensional material in this embodiment and that in embodiment 1 is that the sodium borohydride in embodiment 1 is replaced with the same molar amount of boron powder, the 50 mL distilled water solvent is replaced with 50 mL NMP, and in addition, ethanolamine is added instead of CTAB. The reaction conditions are changed to 0° C. reaction for 4 hours in a homogeneous reactor, and the other parameters are the same as those in embodiment 1.
[0039] Example 4
[0040] The preparation of niobium boride-niobium oxide composite three-dimensional material in this embodiment is different from that in Embodiment 1 in that the niobium pentachloride in Embodiment 1 is replaced by the same molar amount of ammonium niobate oxalate, the sodium hydroxide is replaced by potassium hydroxide, and in addition, ethanolamine is added instead of CTAB. The other parameters are the same as those in Embodiment 1.
[0041] Example 5
[0042] The preparation of niobium boride-niobium oxide composite three-dimensional material in this embodiment is different from that in Embodiment 1 in that the 50 mL distilled water solvent in Embodiment 1 is replaced with 50 mL oleylamine, and the sodium borohydride is replaced with the same molar amount of boron dioxide, and the other parameters are the same as in Embodiment 1.
[0043] The preparation method of the present invention is simple, low-cost, and has low requirements for equipment. For the first time, a three-dimensional material of niobium boride-niobium oxide composite (NbB-NbO2) is prepared, which utilizes the unique advantages of the interface of heterogeneous materials to prevent the catalyst from being passivated, combines the built-in electric field effect of the heterogeneous interface, improves the bonding ability with polysulfides, and improves the charge transfer kinetics, promotes the transformation of elemental sulfur to polysulfides, inhibits the "shuttle effect" of lithium-sulfur batteries, and enhances the long cycle life and rate performance of lithium-sulfur batteries at low temperatures. At the same time, niobium boride-niobium oxide composite materials can also be used in the negative electrode of lithium-ion battery materials, showing high discharge capacity and fast charging characteristics, and have good application prospects.
[0044] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a niobium boride-niobium oxide composite three-dimensional material, characterized in that: The following steps are involved: The niobium source and the boron source are dissolved in a solvent containing an alkaline solution in a molar ratio of 1:1.2-2.3, a surfactant is added, and the reaction is stirred under a protective atmosphere. After the reaction is completed, the product is washed and dried to obtain a niobium boride-niobium oxide composite three-dimensional material.
2. The method according to claim 1, characterized in that: The niobium source includes one of niobium pentachloride, niobium ethanol, niobium oxalate, ammonium niobate oxalate and niobium pentoxide; the boron source includes one of boron dioxide, sodium borohydride and boron powder; the alkaline solution includes one or more combinations of sodium hydroxide, potassium hydroxide and ammonia water; the solvent includes one or more combinations of ultrapure water, oleylamine, ethanol, cyclohexane, isopropanol, glycerol, tetrahydrofuran, N-methylpyrrolidone and ethylene glycol; the surfactant includes one or more combinations of hexadecyltrimethylammonium bromide, ethanolamine and polyvinylpyrrolidone.
3. The method according to claim 1, characterized in that: The amount of alkaline substance in the alkaline solution is 0.5-2 times the molar ratio of the niobium source, and the amount of surfactant is 0.4-3 times the molar ratio of the niobium source.
4. The method according to claim 1, characterized in that: The stirring reaction temperature is 0-120°C and the time is 3-24h.
5. An application of a niobium boride-niobium oxide composite three-dimensional material prepared by the method according to any one of claims 1 to 4, characterized in that: The niobium boride-niobium oxide composite three-dimensional material is used as a host material of sulfur in a lithium-sulfur battery or as a catalyst alone to adsorb polysulfides.
6. The use according to claim 5, characterized in that: When used in lithium-sulfur batteries, the niobium boride-niobium oxide composite three-dimensional material is evenly mixed with graphyne to form a composite material, the composite material and the active material sublimated sulfur are ground and mixed into a uniform powder, which is transferred into a polytetrafluoroethylene reactor or a magnetic boat, heated to 140-170°C for constant temperature reaction, and a mixture of sulfur, niobium boride-niobium oxide and graphyne is obtained, which is used as the positive electrode material of the lithium-sulfur battery.
7. The use according to claim 6, characterized in that: The mass ratio of the niobium boride-niobium oxide composite three-dimensional material to graphyne is 1:2-5, and the mass ratio of the composite material to the active material sublimated sulfur is 2-4.5:6.5-8.
5.
8. The use according to claim 6, characterized in that: Use a forced air drying oven or a tube furnace to heat to 140-170°C and maintain a constant temperature reaction time of 4-20 hours.
9. An application of a niobium boride-niobium oxide composite three-dimensional material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The niobium boride-niobium oxide composite three-dimensional material is used as a negative electrode active material in a lithium ion battery.
10. The use according to claim 9, characterized in that: The niobium boride-niobium oxide composite three-dimensional material is dispersed in a solvent as a negative electrode active material with a conductive agent and a binder to obtain a negative electrode slurry, and the negative electrode slurry is coated on a current collector, and is heated, dried, rolled, and punched to obtain a negative electrode sheet.
Citation Information
Patent Citations
Preparation method of nano niobium boride powder
CN103950946A
Multi-composite-crystal-phase magnetic conductive glass and preparation method thereof
CN117342789A
Niobium boride-niobium carbide composite ceramic as well as preparation method and application thereof
CN117865684A
Surface passivation technology for improving electrochemical performance of niobium diboride
CN118867239A
Acicular boride powder, method for producing the same, and, electrode catalyst for fuel cell
JP2009215155A